Democracy and digital disintegration: Platforms, actors, citizens - Widholm Andreas; Ekman Mattias (Nordicom Review)
The digital transformations of contemporary media systems have had severe consequences for democracy and public debates. This introductory article addresses key challenges of what we refer to as varieties of “digital disintegration” within democratic societies. The eight contributions in the special issue are thematised in three parts. The first part explores disintegration within the context of political communication during elections, including data-driven campaigning, populism, and politicised forms of news production. The second part delves into the role of alternative news curators, audience polarisation, and issues of self-censorship in digital information environments. The third part centres on deliberative norms connected to content moderation of user comments within legacy media and the consequences digitalisation has had on journalistic sourcing practices and source diversity over time. The contributions offer valuable empirical insights, as well as new lines of thinking concerning democracy and digital and disintegrative transformations in the Nordic region and beyond.